Implementation of the Singular Therapeutic Plan in Primary Care: Strengths and potential obstacles (Research, Society and Development, 2023)
The present article seeks to report facilitating and hindering factors in the implementation of the Singular Therapeutic Plan (PTS) in Primary Care from the perspective of healthcare professionals. It is an exploratory, descriptive, and cross-sectional study with a qualitative approach. The study was conducted with 15 preceptors/healthcare professionals from Primary Care in Pontal do Araguaia (MT). Thematic analysis yielded the following categories: strengths for PTS implementation and potential obstacles. In the context of their healthcare work in their respective territories, healthcare service professionals identified resolution, bonding, comprehensiveness, collaborative interprofessional practice, and user-centered care as motivating factors for implementation. Meanwhile, the lack of ownership/commitment, absence of planning, and workload were perceived as potential obstacles by the professionals. In summary, the results obtained will serve as a foundation for guiding the implementation of PTS in the municipality's Primary Care and in other Health Departments, given that facilitative elements for its effectiveness have been identified, as well as the obstacles.